2016
DOI: 10.1158/1541-7786.mcr-16-0075
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial β-Carotene 9′,10′ Oxygenase Modulates Prostate Cancer Growth via NF-κB Inhibition: A Lycopene-Independent Function

Abstract: Despite numerous inquiries into protective roles of lycopene in prostate cancer prevention or therapy, little is known about mechanisms by which lycopene or its metabolites inhibit prostate cancer. The enzyme b-carotene 9',10'-oxygenase (BCO2), which catalyzes asymmetric cleavage of several carotenoids, is the principal regulator of lycopene metabolism, but the range of BCO2 biological functions is incompletely understood. This study investigated expression and functional roles of BCO2 in human prostate cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 50 publications
0
38
3
1
Order By: Relevance
“…In the TRAMP mice fed a control AIN diet, we do not detect an impact of Bco2−/− compared to Bco2+/+ genotype. There is new evidence that exogenous Bco2 expression leads to inhibition of prostate cancer cell growth in vitro , in a lycopene- and enzyme activity-independent manner, (59) highlighting a potential BCO2 function in prostatic tissue, that was not detectable in the TRAMP system designed to test prevention. When fed tomato or lycopene, we see an attenuation of the anticancer effect in the Bco2−/− compared to Bco2+/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the TRAMP mice fed a control AIN diet, we do not detect an impact of Bco2−/− compared to Bco2+/+ genotype. There is new evidence that exogenous Bco2 expression leads to inhibition of prostate cancer cell growth in vitro , in a lycopene- and enzyme activity-independent manner, (59) highlighting a potential BCO2 function in prostatic tissue, that was not detectable in the TRAMP system designed to test prevention. When fed tomato or lycopene, we see an attenuation of the anticancer effect in the Bco2−/− compared to Bco2+/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that there is an inverse association between the occurrence of pancreatic cancer and dietary lycopene intake together with vitamin A and β-carotene [70]. β-Carotene 9′,10′-oxygenase which is a key enzyme for the metabolism of lycopene has been proposed to have an important roles to prevent prostate cancer progression by inhibiting NF-κB signaling [71].…”
Section: Antioxidant Functions Of Carotenoids At Molecular Level For mentioning
confidence: 99%
“…Variants at the BCO2 locus are associated with the IL-18 level, but not carotenoids in either plasma or macula (20). Studies have revealed that mutations in human BCO2 have been linked to macular degeneration (21), insulin resistance and obesity (22), and prostate cancer (23). Further, the loss of BCO2 protein expression is associated with the development of anemia in zebrafish, though the anemia results not from impaired erythropoiesis, but instead from increased apoptosis of erythrocyte precursors (24).…”
Section: Introductionmentioning
confidence: 99%